The Effect of English Conversation Practice Application On the Students' English-Speaking Proficiency in Tenth Grade Students of Senior High School - Ahnaf Farhan Rifqillah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
English language education in Indonesia has a strong background as part of the formal curriculum at various levels of education. English is considered important for supporting global communication skills and access to science and technology. However, this education faces various fundamental problems, such as low teaching quality due to a lack of competent teachers, limited learning resources, and a learning approach that is still predominantly theoretical without adequate practice. Students in Indonesia face challenges in learning English due to the lack of exposure to English in their daily lives, which makes it difficult for them to master speaking and listening skills. In addition, learning methods that are not interactive and the lack of supporting facilities such as books, interactive media, and digital technology also hinder the learning process. This condition is exacerbated in remote and underdeveloped areas where it is difficult to access quality learning materials and competent teachers. Advances in technology bring both challenges and opportunities to English language learning. The main challenge is the uneven readiness of infrastructure and resources, meaning that not all schools are able to integrate technology into their teaching. However, educational technology such as online learning applications and interactive platforms also opens up opportunities for more engaging and effective learning, including interaction with native speakers through virtual classrooms. The phenomenon that supports the evidence of these problems can be seen from the gap in English language skills between regions, low student motivation and interest, and the lack of relevant and contextual learning materials in many schools. To address this issue, TalkEnglish.com introduced the English Conversation Practice application, which allows students to practice daily conversations and engage in conversations with a bot that coordinates the flow of conversation automatically. Previous research has shown that using English Conversation as a learning medium can significantly improve speaking skills. This study aimed to examine the effect of using the English Conversation Practice application on the tenth-grade students' English-speaking proficiency in senior high school.
Reaploud Repository 16 Maret_agus
Keywords: Practice; Conversation; Speaking Ability